Development of e-modules of basic laws of chemistry based on problem-based learning to improve critical thinking skills - Leny, Leny; Wahidah, Wahidah; Mahdian, Mahdian; Kusasi, Muhammad (Universitas Negeri Yogyakarta, 2024)
Critical thinking is an important aspect of the skills expected in 21st-century learning, especially in chemistry learning. Based on preliminary studies that have been carried out, critical thinking skills are still not practiced in the learning process, and the teaching materials used are still only a few that relate daily life problems to the material. This study aimed to evaluate the validity, practicality, and effectiveness. The ADDIE model was used as the method of this research, 36 students of class X-E of Senior High School 5 Banjarmasin were the subjects of the development research. Data were collected with test and non-test instruments. Analysis of validity, practicality, and effectiveness were the analysis techniques used in this study. The findings of this study are that the e-module has a very high level of validity which is 94.93, very practical with a practicality score of 84.46, and effective with an N-Gain of 81.15. Suggestions for future researchers are that the developed e-modules can be accessed without using the internet and the testing of the developed products can be more than one school.